Ultrasound-Guided Peripheral Nerve Blocks Performed by Orthopedic Surgeons: A Retrospective, Multicenter Study in Akita Prefecture, Japan - Tatsuru Tomioka; Seietsu Senma; Yuichiro Narita; Masakazu Urayama; Satoshi Yumoto; Hiroki Ito; Toshiaki Aizawa; Tsuyoshi Shirahata; Hiroshi Aonuma; Nozomi Kaga; Norimitsu Masutani; Yusuke Yuasa; et al. (Advances in Orthopedics)
The shortage of doctors is a societal problem, especially in rural areas such as Akita Prefecture, Japan. Therefore, it is not unusual in Akita for orthopedic surgeons to perform upper and lower limb surgeries under ultrasound-guided peripheral nerve blocks managed by the operators themselves. Multicenter studies of ultrasound-guided peripheral nerve blocks performed by orthopedic surgeons have not been reported. The purpose of this study was to clarify the safety and reliability of ultrasound-guided peripheral nerve blocks performed by orthopedic surgeons in Akita. A total of 1,674 upper extremity surgery cases operated under ultrasound-guided peripheral nerve blocks at 8 hospitals in Akita prefecture from April 2016 to April 2018 were investigated retrospectively. These blocks were performed by a total of 37 orthopedic surgeons, including senior surgeons and residents. In 321 of the 1,674 cases (19%), local anesthetics were added to the surgical field. Two cases with special factors were converted to general anesthesia. There were 2 cases of complications associated with the nerve block, but they were all transient and recovered promptly. The block site and the hospital where the block was performed showed a significant relationship with the addition of local anesthetics to the surgical site (P<0.001). Surgery time, age at surgery, and surgical site showed no significant relationships with the addition of local anesthetics. The volume of the anesthetic used for the nerve block showed a significant inverse relationship with the addition of local anesthetics (P=0.040). Many orthopedic surgeons in Akita prefecture began to perform ultrasound-guided peripheral nerve blocks, which had a reliable anesthesia effect with no noticeable complications, whether performed by residents or senior orthopedic surgeons, and this is a useful anesthetic technique for orthopedic surgeons.